Effects of tapering with light vs. heavy loads on track and field throwing performance - Zaras, N. D.; Stasinaki, A.-N. E.; Krase, A. A.; Methenitis, S. K.; Karampatsos, G. P.; Georgiadis, G. V.; Spengos, K. M.; Terzis, G. D. (The Journal of Strength and Conditioning Research, 2014)
The purpose of the study was to investigate the effects of power training with light vs. heavy loads during the tapering phases of a double periodized training year on track and field throwing performance. Thirteen track and field throwers aged 16-26 years followed 8 months of systematic training for performance enhancement aiming at 2 tapering phases during the winter and the spring competition periods. Athletes performed tapering with 2 different resistance training loads (counterbalanced design): 7 athletes used 30% of 1 repetition maximum (1RM) light-load tapering (LT), and 6 athletes used the 85% of 1RM heavy-load tapering (HT), during the winter tapering. The opposite was performed at the spring tapering. Before and after each tapering, throwing performance, 1RM strength, vertical jumping, rate of force development (RFD), vastus lateralis architecture, and rate of perceived exertion were evaluated. Throwing performance increased significantly by 4.8 ± 1.0% and 5.6 ± 0.9% after LT and HT, respectively. Leg press 1RM and squat jump power increased more after HT than LT (5.9 ± 3.2% vs. -3.4 ± 2.5%, and 5.1 ± 2.4% vs. 0.9 ± 1.4%, respectively, p < 0.05). Leg press RFD increased more in HT (38.1 ± 16.5%) compared with LT (-2.9 ± 6.7%), but LT induced less fatigue than HT (4.0 ± 1.5 vs. 6.7 ± 0.9, p < 0.05). Muscle architecture was not altered after either program. These results suggest that performance increases similarly after tapering with LT or HT in track and field throwers, but HT leads to greater increases in strength, whole body power, and RFD.